Root exudate metabolomes change under drought and show limited capacity for recovery - Gargallo-Garriga, Albert; Preece, Catherine; Sardans, Jordi; Oravec, Michal; Urban, Otmar; Peñuelas, Josep (Scientific reports, 2018)
Root exudates comprise a large variety of compounds released by plants into the rhizosphere, including low-molecular-weight primary metabolites (particularly saccharides, amino acids and organic acids) and secondary metabolites (phenolics, flavonoids and terpenoids). Changes in exudate composition could have impacts on the plant itself, on other plants, on soil properties (e.g. amount of soil organic matter), and on soil organisms. The effects of drought on the composition of root exudates, however, have been rarely studied. We used an ecometabolomics approach to identify the compounds in the exudates of Quercus ilex (holm oak) under an experimental drought gradient and subsequent recovery. Increasing drought stress strongly affected the composition of the exudate metabolome. Plant exudates under drought consisted mainly of secondary metabolites (71% of total metabolites) associated with plant responses to drought stress, whereas the metabolite composition under recovery shifted towards a dominance of primary metabolites (81% of total metabolites). These results strongly suggested that roots exude the most abundant root metabolites. The exudates were changed irreversibly by the lack of water under extreme drought conditions, and the plants could not recover.
Keywords: Quercus; období sucha; Plant Exudates; Metabolome; metabolom; Plant Roots; rostlinné exsudáty; kořeny rostlin; Droughts; dub (rod)